2015
DOI: 10.1002/2014jb011617
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic and sedimentary controls on widespread gas emissions in the Sea of Marmara: Results from systematic, shipborne multibeam echo sounder water column imaging

Abstract: Understanding of the evolution of fluid-fault interactions during earthquake cycles is a challenge that acoustic gas emission studies can contribute. A survey of the Sea of Marmara using a shipborne, multibeam echo sounder, with water column records, provided an accurate spatial distribution of offshore seeps. Gas emissions are spatially controlled by a combination of factors, including fault and fracture networks in connection to the Main Marmara Fault system and inherited faults, the nature and thickness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 85 publications
(238 reference statements)
2
118
0
Order By: Relevance
“…The Sea of Marmara is also characterized by a large number of widespread gas expulsion sites at the seafloor, bubbling up to several tens to hundreds of meters into the water column [ Burnard et al ., ; Dupré et al ., ; Gasperini et al ., ; Géli et al ., ; Kuscu et al ., ; Tary et al ., ; Zitter et al ., ]. Such gases are primarily of thermogenic origin in the western Marmara, which is geologically connected to the hydrocarbon reservoirs of the Thrace basin, while mainly biogenic gases, i.e., generated by microbial activity, have been collected from the seafloor of the Cinarcik Basin and the Gulf of Izmit (Figure ) [ Bourry et al ., ; Gasperini et al ., ; Kuscu et al ., ; Ruffine et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sea of Marmara is also characterized by a large number of widespread gas expulsion sites at the seafloor, bubbling up to several tens to hundreds of meters into the water column [ Burnard et al ., ; Dupré et al ., ; Gasperini et al ., ; Géli et al ., ; Kuscu et al ., ; Tary et al ., ; Zitter et al ., ]. Such gases are primarily of thermogenic origin in the western Marmara, which is geologically connected to the hydrocarbon reservoirs of the Thrace basin, while mainly biogenic gases, i.e., generated by microbial activity, have been collected from the seafloor of the Cinarcik Basin and the Gulf of Izmit (Figure ) [ Bourry et al ., ; Gasperini et al ., ; Kuscu et al ., ; Ruffine et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent long‐term monitoring experiment carried out close to the eastern termination of the 1999 Mw = 7.4 Izmit earthquake has confirmed the potential of combining seismological and gas‐geochemical observations of the seafloor to study the seismic cycle [ Embriaco et al ., ]. Previous studies of the water column in the Sea of Marmara have shown a systematic association between fluid expulsion sites along the North Anatolian Fault and the fault network, and the basin edges [ Dupré et al ., ; Kuscu et al ., , ]. Thus, those faults play an important role in the migration of deep‐sourced fluids to the seafloor.…”
Section: Introductionmentioning
confidence: 99%
“…Gas migration mechanisms in soft sediments control gas release events (Dupre et al, 2015;Scandella et al, 2017), determine the formation of craters and pockmarks (Andreassen et al, 2017;de Prunele et al, 2017;Riboulot et al, 2016), and constrain the potential gas recovery strategies from methane hydrate accumulations in shallow marine sediments (Fauria & Rempel, 2011;Jang, 2014;Moridis et al, 2011). Gas migration pathways are also relevant to other degassing processes such as subsurface CO 2 leakage (Bang et al, 2013;Cevatoglu et al, 2015;Lewicki et al, 2007) and gas-driven volcanic eruptions (Suckale et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of reduced fluids and evidence for the presence of shallow methane (high sulfide concentrations, bacterial mats) in the Hugin Fracture sediments suggests that fractures may also be important fluid migration pathways in the North Sea. Fault‐related methane seepage structures have mainly been observed in tectonically active areas such as the Marmara Sea (Dupre et al, ), the Santa Barbara Basin (Eichhubl et al, ) and the Nankai Trough (Henry et al, ). Our study shows that the Hugin Fracture is an active conduit transferring fluids from the deeper in the sediment column (<550 m below the seafloor) into surface sediments, with visual and geophysical indicators for near‐surface fluid flow, biogeochemical turnover of methane and large spatial variabilities.…”
Section: Discussionmentioning
confidence: 99%